Tinjauan Tentang Tata Rias Pengantin Modifikasi pada Pengantin Koto Gadang, Sumatera Barat - Azizah, Aulia; Hayatunnufus, Hayatunnufus (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to describe the forms and characteristics of makeup, clothing, and accessories for modified brides from Koto Gadang, West Sumatra. The background of the research is based on the phenomenon of changes in traditional bridal makeup into modifications that combine cultural elements with modern trends, thus generating both pros and cons among the community. This study employs a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The informants include bundo kanduang, makeup artists, and bridal clothing rental business owners in Nagari Koto Gadang. The data analysis techniques used are data reduction, data display, decision making, and verification. The research results show that the modified bridal makeup of Koto Gadang has undergone a transformation from a bold style with bright colors to soft, natural, and flawless makeup using modern techniques such as cut crease, ombre lips, and fiber eyebrow shaping. The modified attire still retains traditional elements such as tilakuang, kodek, and salendang, but is presented in soft colors, with the addition of sequins and the use of kebaya. The modified bridal accessories still follow the typical Koto Gadang form but are used more selectively and many are made from lighter and more affordable alternative materials. The study concludes that the modification of bridal makeup in Koto Gadang is a form of adaptation to the times that still preserves cultural identity, although it potentially reduces the symbolic meaning of traditional forms.